Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Sirup Tjampolay di Pusat Oleh-Oleh Cirebon - Setiawan, Christin; Hidayat, Candra; Gantina, Devita (Jurnal Ilmiah Pariwisata, 2023)
The aim of the research is to determine the influence of brand image and product quality on purchasing decisions for Tjampolay Syrup at the Cirebon Souvenir Center in Cengkareng. This type of research is descriptive quantitative with a simple linear regression analysis method. The sampling technique using saturated sampling technique was used by 100 respondents who were visitors to purchasing Tjampolay Syrup at the Cirebon By-By Center. The research results show that brand image and product quality have a significant influence on purchasing decisions. A brand image that is linked to local and cultural identity succeeds in forming emotional bonds, strengthening trust and increasing consumer preferences. The integration of product quality with cultural heritage creates a more meaningful experience, gives consumers a strong reason to choose it, and strengthens the brand's positive image in competition in the local market. Tjampolay Syrup at the Cirebon Souvenir Center and influencing purchasing decisions, it is recommended to maintain the quality of raw materials and production processes, consider quality certification, present product variants or innovations according to customer needs, design attractive packaging that reflects the brand image, provide clear information about the product , advantages, and how to use it, as well as utilizing social media and online marketing to build their fan community. Keywords: Brand Image, Product Quality, Purchasing Decisions